Characteristics of secondhand electronic cigarette aerosols from active human use. Issue 12 (2nd December 2017) - Zhao, Tongke; Nguyen, Charlene; Lin, Che-Hsuan; Middlekauff, Holly R.; Peters, Kacey; Moheimani, Roya; Guo, Qiuju; Zhu, Yifang
ABSTRACT: The electronic cigarette (EC) is a new source of indoor airborne particles. To better understand the impacts of secondhand vaping (SHV) emissions on indoor air quality, real-time measurements of particle size distribution, particle number concentration (PNC), fine particulate matter (PM2.5 ), CO2, CO, and formaldehyde were conducted before, during, and after 10 min EC-use among 13 experienced users in an 80 m 3 room. To assess particle transport in the room, multiple sampling locations were set up at 0.8, 1.5, 2.0, and 2.5 m away from the subjects. The arithmetic mean (standard deviation) of background PNC and PM2.5 concentrations in the room were 6.39 × 10 3 (1.58 × 10 2 ) particles/cm 3 and 8 (1) μg/m 3, respectively. At 0.8 m away from EC users, right after initiation of puffing, the PNC and PM2.5 concentrations can reach a peak of ∼10 5 particles/cm 3 and ∼3 × 10 3 µg/m 3, respectively, and then dropped quickly to background levels within 20 s due to dilution and evaporation. At the 0.8 m sampling location, the mean PNC and PM2.5 concentrations during puffing were 2.48 × 10 4 (2.14 × 10 4 ) particles/cm 3 and 188 (433) µg/m 3, respectively. In addition, two modes of SHV particles were observed at about 15 and 85 nm. Moreover, concentrations of SHV particles were negatively correlated with the distances to EC users. At the 1.5 m location, PNC and PM2.5 levels were 9.91 × 10 3 (1.76 × 10 3 ) particles/cm 3 and 19 (14) µg/m 3, respectively. Large variations of mean PNC levels exhaled per puff were observed both within and between EC users. Data presented in this study can be used for SHV particle exposure assessment. Copyright © 2017 American Association for Aerosol Research